Reforma evropskega patentnega prava - Pohar, Klemen (Podjetje in delo, 2015)
The reform of the European system of patent protection is a project the EU member states have long attempted to accomplish. Many attempts to implement this reform have so far been unsuccessful, but now it appears that the reform, encompassing the creation of the European patent with unitary effect and the establishment of the unified patent court, will finally be brought into effect. The new system of patent protection will not be as first envisaged and will significantly differ from the typical model of protection of the EU intellectual property rights. The author firstly presents the main and the most disputed characteristics of the new patent system and then he continues with his opinion on the appropriateness of the reform and its implementation.
Keywords: European Union; Evropska unija; intelektualna lastnina; patenti; pravna ureditev